1996
DOI: 10.1096/fasebj.10.2.8641562
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of PG‐H/aggrecan and PG‐M/versican on avian neural crest cell migration

Abstract: Aggrecans and PG-M/versicans represent two newly defined families of hyaluronan-binding proteoglycans for which the function is still poorly understood. Using the avian neural crest as a model system, we have examined the molecular mechanisms entailed in the cell-proteoglycan interaction during embryonic cell motility. Both the primary cartilage aggrecan of the avian embryo (PG-H/aggrecan) and the largest variant of the avian mesenchymal versican (PG-M/versican VO) failed to support neural crest cell adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 8 publications
6
57
0
Order By: Relevance
“…Hyaluronan is crucial for proper trunk NCC migration XHas2-deprived embryos showed altered trunk NCC migration, corroborating a proposed pivotal role of HA during NCC development (Perris et al, 1996;Perris, 1997;Perris and Perissinotto, 2000;Epperlein et al, 2000). In fact, previous experimental evidence from our group have indicated that different local accumulations of HA-versican complexes may define migration-permissive and non-permissive environments for NCC migrating in the trunk region of the embryo (Perris et al, 1991;Perissinotto et al, 2000).…”
Section: Hypaxial Muscle Cells Migration Is Controlled By Xhas2 and Csupporting
confidence: 67%
“…Hyaluronan is crucial for proper trunk NCC migration XHas2-deprived embryos showed altered trunk NCC migration, corroborating a proposed pivotal role of HA during NCC development (Perris et al, 1996;Perris, 1997;Perris and Perissinotto, 2000;Epperlein et al, 2000). In fact, previous experimental evidence from our group have indicated that different local accumulations of HA-versican complexes may define migration-permissive and non-permissive environments for NCC migrating in the trunk region of the embryo (Perris et al, 1991;Perissinotto et al, 2000).…”
Section: Hypaxial Muscle Cells Migration Is Controlled By Xhas2 and Csupporting
confidence: 67%
“…4). Because the bottle-brush structure of monomeric PG-M/versican (46) was not clearly apparent after rotary shadowing electron microscopy of microfibrils (Fig. 2B), perhaps only a portion of versican (containing the mAb 2B1 epitope) remained undegraded and associated with microfibrils following digestion of tissues with crude collagenase.…”
Section: Resultsmentioning
confidence: 99%
“…Versican has been implicated in the regulation of neural crest migration and cardiovascular development (Dutt et al, 2006;Henderson et al, 1997;Landolt et al, 1995;Perissinotto et al, 2000;Perris et al, 1996). Splotch, a Pax3 mutant, is believed to result in part from the overexpression of versican, which results in skin pigmentation and craniofacial defects (Henderson et al, 1997).…”
Section: Genetic Interaction Of Vcan With Adamts20 Implies An Active mentioning
confidence: 99%